Factors Determining Intention to Use Contraception Among Sexually Active Women in South Africa: A Multilevel Modelling Approach - Germinah Motshegwa; Mluleki Tsawe; Onalenna Legotlo; Marinkie Malatji; Shirley Mathabatha; Reamogetse Phateng; Kenneth Pule Tshabalala; Jaqueline Seima; Mary Berries; Tsholofelo Seokamo (Advances in Public Health)
Conclusion: The results showed that age, population group, parity, ideal number of children, desire to delay childbearing, exposure to family planning messages/advice, and province were key predictors of women’s intention to use contraception. The findings suggest the need for targeted education initiatives about contraception, particularly among older women. There is also a need to involve community leaders and the local media in sexual and reproductive health campaigns.